Recent progress of superconducting fault current limiter in China. (10th November 2020) - Zhang, GuoMin; Wang, Haonan; Qiu, Qinggquan; Zhang, Zhifeng; Xiao, Liye; Lin, Liangzhen
Abstract: With the increase of electricity demand and the rapid development of renewable energy generation, it is becoming more and more important to ensure the safety and stability of power grid, where a superconducting fault current limiter (SFCL) could play an important role. In recent years, a lot of research work has been done in China on the application of high temperature superconducting (HTS) power technology, especially in the aspects of superconducting fault current limiting technology, superconducting fault current limiting-breaking technology, superconducting fault current limiting- magnetic energy storage technology, and superconducting fault current limiting transformer technology. A number of demonstration projects on SFCL were also conducted. In this paper, the research progress of HTS fault current limiters (both AC and DC) in China in recent years is introduced, including the completed projects and the on-going work. The possible application direction of SFCL in the future is proposed.